Pelatihan Digital Marketing di Pondok Pesantren Darullughah Wadda’wah, Bangil, Pasuruan - Abidin, Zainal (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2024)
This research explores the potential for empowering digital marketing at the Darullughah Wadda'wah Islamic Boarding School, Bangil, Pasuran, as an innovation to improve the community's economy. By using participatory action research (PAR) methods, this research identifies that through implementing digital marketing strategies, Islamic boarding schools can have a significant positive impact on the skills and economic independence of students. The implications of this research highlight the importance of active collaboration between Islamic boarding schools and local communities to achieve success in efforts to empower the community's economy.